Faktor yang Mempengaruhi Kejadian Dermatitis pada Pengangkut Sampah - Filda, Sri; Tosepu, Ramadhan (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
Dermatitis, known as eczema, is a skin disease that attacks parts of the epidermis and can cause acute or even chronic nature. Dermatitis affects reduced productivity and health of workers who play a role in spreading diseases such as poor personal hygiene, unhygienic environments, and unhealthy behavior. The purpose of this article is to find out the factors that influence the occurrence of dermatitis in Kendari City. The study was conducted using data on the number of cases last year 2023 in Kendari City, this data was obtained directly from the Health Department of Kendari City. Further from the data that has been acquired, the researchers looked at the movement of the number of cases of dermatitis that occurred in the period of last year that is January to December then compared and found out factors that affect the appearance of cases of Dermatitis. The results of this study show that the factors that influence the occurrence of dermatitis in the City of Self include personal hygiene and the use of self-protection equipment (APD). It is expected that garbage carriers can implement a clean and healthy lifestyle (PHBS) to avoid the risk of developing dermatitis.